The Norwegian Sea Gyre – A Regulator of Iceland-Scotland Ridge Exchanges - Hátún, Hjálmar; Chafik, Léon; Larsen, Karin Margretha Húsgarð (Frontiers in Marine Science, 2021)
The Norwegian Sea gyre (NSG) is a large body of Arctic intermediate water and deep dense overflow waters, which circulate counterclockwise within the Norwegian Sea. Argo float trajectories presented in this study suggest that the NSG attains its strongest and most focused flow downstream of a confluence of subarctic waters from the Iceland Sea and the Jan Mayen Ridge at steep bathymetry north of the Faroe slope. Based on hydrographic data from a meridional standard section across this flow (1988 to present), the first baroclinic estimate of the NSG circulation strength is provided. We, furthermore, show that the NSG circulation regulates key aspects of both the poleward Atlantic Water (AW) currents and the equatorward near-bottom and mid-depth flows in the Norwegian Sea – the main arteries of the Meridional Overturning Circulation. More specifically, we demonstrate close links between the NSG circulation and (i) the observed Faroe Bank Channel Overflow (FBCO) transport, (ii) variable depth of the main thermocline separating AW from the underlying colder and denser subarctic water masses, and (iii) satellite-derived sea-surface heights (SSHs) in the southern Nordic Seas. In general, a strong NSG and weak FBCO transport are associated with an uplifted thermocline and depressed SSH. Along a narrow band near the Norwegian and Shetland slopes, a strong NSG – oppositely – links to a depressed interface. Daily records of the FBCO transport, and satellite altimetry in a sensitive region north of the Iceland-Faroe Ridge, complement our hydrographic monitoring of the NSG strength. Together these records constitute valuable indicators for aspects of the Norwegian Sea physical oceanography, which likely have an impact on regional climate, ecology and biological productivity.